2011
DOI: 10.1182/blood-2010-04-277921
|View full text |Cite
|
Sign up to set email alerts
|

T-cell immune responses to Wilms tumor 1 protein in myelodysplasia responsive to immunosuppressive therapy

Abstract: Clinical observations and laboratory evidence link bone marrow failure in myelodysplastic syndrome (MDS) to a T cellmediated immune process that is responsive to immunosuppressive treatment (IST) in some patients. Previously, we showed that trisomy 8 MDS patients had clonally expanded CD8 ؉ T-cell populations that recognized aneuploid hematopoietic progenitor cells (HPC). Furthermore, microarray analyses showed that Wilms tumor 1 (WT1) gene was overex-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 55 publications
2
45
0
Order By: Relevance
“…KA2 cells and KA2 cells pulsed with the WT1 126-134 peptide were not efficient targets for the expanded T cells. This indicated that the anti-WT1 cytotoxic reactivity seems to be highly dependent on the level of WT1 endogenous presentation by the target cells, which is an important consideration, since hematopoietic stem and progenitor cells express lower levels of WT1 than leukemia cells (Sloand et al, 2011). T-cell expansion and anti-WT1 reactivity were highly correlated for both the analyses performed with samples obtained from the healthy donor and the AML patient.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…KA2 cells and KA2 cells pulsed with the WT1 126-134 peptide were not efficient targets for the expanded T cells. This indicated that the anti-WT1 cytotoxic reactivity seems to be highly dependent on the level of WT1 endogenous presentation by the target cells, which is an important consideration, since hematopoietic stem and progenitor cells express lower levels of WT1 than leukemia cells (Sloand et al, 2011). T-cell expansion and anti-WT1 reactivity were highly correlated for both the analyses performed with samples obtained from the healthy donor and the AML patient.…”
mentioning
confidence: 79%
“…Nevertheless, mice did not show any signs of progressive generalized autoimmunity or toxicity. For SmartDC/tWT1, since it was recently shown that patients with trisomy 8 with myelodypsplastic syndrome (MDS) show detectable levels of CD8 + T-cell responses directed against WT1 in hematopoieitic progenitor cells, a hypothetical concern would be that the potent anti-WT1 immune response generated by SmartDC/tWT1 could lead to reactivity against hematopoietic progenitor cells and myelosuppression (Sloand et al, 2011). This biosafety concern remains to be evaluated in immune-competent mouse models or in immune-deficient mice reconstituted with human hematopoietic stem cells.…”
mentioning
confidence: 99%
“…53 In addition, a relationship between T-bet overexpression and BM failure has been demonstrated in patients with aplastic anemia and MDS. 9,[54][55][56][57][58] It is worthwhile mentioning that Sca-1 becomes aberrantly expressed and some of the HSCs in this case are in fact myeloid progenitors, when IFNs are upregulated as in the current transgenic mouse. 59,60 Taking these previous reports into account, there could have been an increase in the frequency of myeloid progenitors in the BM of T-bet tg mice, which is also in line with the result of the CFC assay.…”
Section: Blood 8 January 2015 X Volume 125 Number 2 Aberrant T Cellmentioning
confidence: 99%
“…2 Laboratory and clinical findings in studies of myelodysplasia in adults suggest that autoimmunity directed against hematopoietic stem cells contributes to the development of cytopenia in MDS. [3][4][5][6][7] In addition, it is generally believed that there is a pathophysiological overlap between aplastic anemia and hypocellular MDS. 8 These concepts have led to the use of immunosuppressive therapy (IST), which has proven to be effective in some adults with MDS.…”
Section: Introductionmentioning
confidence: 99%